Internet of Things (IoT) Based Neonatal Incubator for Heart Rate Monitoring and Caregiver Motion Detection - Abdullah, Mastura; Huong Kah Ching, Audrey (Evolution in Electrical and Electronic Engineering, 2024)
The IoT-based health monitoring system has transformed healthcare by enabling seamless real-time tracking of vital health parameters. Using affordable and low-power sensors, it gathers and transmits crucial data on heart rate and oxygen to healthcare providers for analysis. The systems diverse sensors perform well under various conditions, recording BPM readings of 60-100 at rest and 40-60 during occlusion, along with SpO2 values of 95%-100% at rest and 85%-95% during occlusion. Motion detection functionally successfully identifies objects ir caregivers within its proximity. This integration in infant health monitoring signifies a significant advancement with implications for future innovations in neonatal care. The wireless connectivity via Blynk enables remote monitoring with immediate alerts for healthcare providers. Through performance evaluation guarantees measurement reliability, secure data transmission, and algorithmic provide actionable insight.